Vascular ultrastructural changes in hypertensive rodent models: a 15-year scoping review - Ismawi, Hidayatul Radziah; Zulkiflee, Khodijah; Yusoff Azmi Merican, Yusoff Sharizal; Mohd. Zainudin, Maizura; Abd. Fuaat, Azliana; Zainal Abidin, Fadhilah (Universiti Putra Malaysia Press, 2025)
Understanding ultrastructural changes in vascular tissue provides critical insights into the pathophysiology of hyper-tension, a leading global cause of mortality. This scoping review aims to offer a comprehensive overview of vascular ultrastructural changes in hypertensive rodent models over the past 15 years. Following the Arksey and O’Malley protocol, we conducted a scoping review of relevant literature. This involved defining research questions, identifying and selecting pertinent studies, data extraction, synthesis, and reporting. Searches encompassed Google Scholar, PubMed, Scopus, and Science Direct. Thirty studies were included, showcasing diverse methodologies, objectives, and findings. These studies investigated various hypertensive models, different vessels, and multiple quantitative, semi-quantitative, and qualitative parameters of vascular ultrastructure, along with different intervention strategies. This review provides a synthesis of existing knowledge on vascular ultrastructural changes in hypertensive rodent models and discusses relevance of rodent models to human hypertension, functional implications of ultrastructural changes and pharmacological interventions targeting these changes thus serving as a resource for researchers studying hypertension pathophysiology to identify therapeutic targets or assess novel interventions.